THE IMPACT OF ENGLISH LANGUAGE ON THE EXISTENCE OF INDONESIAN LANGUAGE IN THE AGE OF GLOBALIZATION - Lutfi, Revi Septiani (LITERA : Jurnal Bahasa Dan Sastra, 2023)
Globalization is not only disseminating information and technology to develop the human life, but it also brings cultures with new languages ​​which are then absorbed and utilized by people. Likewise, English has turned into an international language which is able to be mastered by various Indonesian people. This research aimed to raise public awareness to uphold the Indonesian language amidst globalization. The result of this study revealed that the flow of globalization affects all aspects of life in the fields of education, culture, and others. Indonesia will not face easy problems, one of which is a threat to national identity or the Indonesian language in the era of globalization. The threat comes in the form of the rapid development of mastery of English which affects the existence of Indonesian language. Its use threatens the existence of the Indonesian language, but its use is also needed in the current era of globalization as one of the basic capitals to be able to compete in the era of globalization.